Molecularly imprinted monoliths: Recent advances in the selective recognition of biomacromolecules related biomarkers. Issue 8 (5th January 2022) - Song, Qingmei; Wang, Bingwu; Lv, Yongqin
Abstract: Biomarkers are significant indicators to assist the early diagnosis of diseases and assess the therapeutic response. However, due to the low abundance of biomarkers in complex biological fluids, it is highly desirable to explore efficient techniques to attain their selective recognition and capture before the detection. Molecularly imprinted monoliths integrate the high selectivity of imprinted polymers and the rapid convective mass transport of monoliths, and as a result, are promising candidates to achieve the specific enrichment of biomarkers from complex samples. This review summarizes the various imprinting approaches for the preparation of molecularly imprinted monoliths. The state‐of‐art advances as an effective platform for applications in the selective capture of biomacromolecules related biomarkers were also outlined.